Indian anthropologists and informants: impossible dialogue in the new Mexican context? (Revista LIDER, 2020)
This essay proposes to question, from the particular methodology of Anthropology, the complexity of the dialogue between a professional anthropologist and indigenous informants who, in this case, are intellectuals formed in institutes and higher educational schools of the country. Equally, these informants are intellectuals in the sense that they think about their realities, difficulties, successes and failures in their dialogues with political authorities in the entities where they live, as well as with the social science researcher. They may or may note benefit from academic or official recognition. They are called ―organic intellectuals‖ who find their base in the indigenous social movements.